2003
DOI: 10.1097/00004424-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Comparative Antithrombotic Effects of Ioxaglate and Iohexol and Interaction With the Platelet Antiaggregant Clopidogrel

Abstract: These data show a greater in vivo antithrombotic potential for the ionic contrast medium ioxaglate than for the non-ionic contrast medium iohexol and, for the first time, a synergistic effect between a contrast medium and a platelet antiaggregant drug in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The thrombosis model was established as previously described, with some modification [24,25]. In brief, male Sprague-Dawley rats, anesthetized with chloral hydrate (0.3 g/kg), were fixed in the supine position.…”
Section: Injury-induced Thrombosis Modelmentioning
confidence: 99%
“…The thrombosis model was established as previously described, with some modification [24,25]. In brief, male Sprague-Dawley rats, anesthetized with chloral hydrate (0.3 g/kg), were fixed in the supine position.…”
Section: Injury-induced Thrombosis Modelmentioning
confidence: 99%
“…Several experimental studies have demonstrated nonionic contrast media to have greater potential for thrombus formation, thrombin generation, and platelet activation than ionic contrast media [4][5][6], but all nonionic media may not share the same thrombogenic potential. The nonionic isosmolar dimer iodixanol appears to have less thrombogenic potential and more favorable effects on endothelial cells than the nonionic low osmolar monomer iohexol [14].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nonionic low osmolar contrast agents, high osmolar ionic contrast agents have been shown to increase the risk of adverse cardiac events during coronary angiography [1][2][3]. However, a greater in vivo antithrombotic potential, a systemic antiplatelet effect, and a lower thrombin generation and a lower activation of the platelet effect have been reported with ionic than with nonionic low osmolar contrast media [4][5][6]. Similarly, in vitro studies have shown that prevention of thrombin formation and platelet activation was only achieved with ionic low osmolar and not with nonionic isosmolar contrast [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although contrast media (CMs) are essential for X-ray angiography, intravascular injection of CMs may cause adverse effects, such as pain, ventricular fibrillation, and nephropathy (1,2,7,21,32).…”
mentioning
confidence: 99%
“…Renal injury can be caused by all CMs, but the degree of nephrotoxicity varies between different CMs, and osmolality plays a big role (6). Antithrombotic activity is not greater with ionic ioxaglate, but anticoagulant activity is (21). On the other hand, there is less nephrotoxicity with iso-osmolar CMs than with low-osmolar CMs (1).…”
mentioning
confidence: 99%